Jan Alan Bardziński – dominikanin, kaznodzieja, tłumacz. Próba nakreślenia sylwetki twórczej - Rusnak, Radosław (Tematy i Konteksty, 2014)
The article casts light on a poorly known and rarely appreciated figure of a late-Baroque Dominican, keen preacher and devoted translator of both laic and religious texts, Jan Alan Bardziński. The author firmly states that Bardziński’s literary activity remains strongly connected to his multiple duties as a monk as one of the main values he searches for in his readings is a didactic one. Nevertheless he certainly can be defined as a consistent adapter of some renowned ancient works as well, which puts him among other 17th and 18th century followers of the humanistic and classicist traditions and enables us to rank high his erudition and philological preparation. The essay makes a brief survey of his works, describing their content and underlining some important notes given by the translator himself regarding his goals and prorities. Some general observations on the characteristics of his texts are made and the question of integrity or disintegrity of his literary production is highlighted as well.